2023
DOI: 10.3390/ijms24076400
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming the Circadian Dynamics of Epileptic Genes in Mouse Temporal Lobe Epilepsy

Abstract: Temporal lobe epilepsy (TLE) is a common and severe epilepsy displaying rhythmicity in humans and animals. However, how the circadian clock contributes to TLE remains elusive. A recent circadian analysis of the ventral hippocampal transcriptome of pilocarpine-induced TLE mice revealed as many as 1650 rhythmically expressed transcripts. Here, a comparison of the mouse ventral hippocampal transcriptome with the human epilepsy-related gene set identified 315 possible mouse epilepsy-related genes. Rhythmicity anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Although epileptic seizures appear as random events, clinical data, patient journals, and basic research have shown that seizures occur more often at certain times over the circadian cycle (Hofstra et al, 2009; Karoly et al, 2021; Sun and Wang, 2023; Zhang et al, 2021). The investigation of cycles from circadian to circannual is becoming an important research topic due to the prospect of chronotherapy – the administration of drugs when they are most effective.…”
Section: Discussionmentioning
confidence: 99%
“…Although epileptic seizures appear as random events, clinical data, patient journals, and basic research have shown that seizures occur more often at certain times over the circadian cycle (Hofstra et al, 2009; Karoly et al, 2021; Sun and Wang, 2023; Zhang et al, 2021). The investigation of cycles from circadian to circannual is becoming an important research topic due to the prospect of chronotherapy – the administration of drugs when they are most effective.…”
Section: Discussionmentioning
confidence: 99%